The Team Work Equipment Sdn.Bhd / Dzul Hizzam Zainal … [et al.] - Zainal, Dzul Hizzam; Elias, Elianis; Mohamed, Maizatul Kamisah; Ku Mohamad, Ku Siti Aishah; Nan, Norazila; Abd.Razak, Noor Shahida; Abd.Razak, Md Razis (2003)
The Team Work Equipment Sdn. Bhd will be establish on January 2004. The Team Work Equipment Sdn. Bhd are located at No.15, Jalan Togo 8, Taman Perindustrian Togo,Sri Damansara, 52200 Kuala Lumpur, Malaysia. Our main focus is serving, supply and rental of lighting, grip and camera for future film and commercial producer who are shooting especially in Klang Valley. In addition, today many new production houses don't have enough equipment for shooting and do their project performance. This location is chosen because it's strategic place nearby a production at Klang Valley. More over entertainment industry are developing in Malaysia. This business will be open on 1st January 2004 to production house, future film and commercial.